Behavioral Science Meets Public Health: A Scoping Review of the Fogg Behavior Model in Behavior Change Interventions - Duarte-Anselmi, G (BioMed Central Ltd, 2025)
Background: Behavior change is essential for promoting health and preventing illness; yet, motivating individuals to adopt and maintain healthy behaviors remains a significant challenge. Multiple models have been developed in Psychology and Behavioral Sciences to understand and encourage behavior change, including the Capability, Opportunity, Motivation, Behavior model (COM-B model), the Health Belief Model, the Behavior Change Wheel, the Theoretical Domains Framework (TDF), nudge theory, and Behavior Change Techniques (BCTs). Among these, the Fogg Behavior Model (FBM), developed by Dr. BJ Fogg, offers a specific and valuable framework for facilitating behavior change. This scoping review aims to analyze studies that apply the FBM in health, particularly its impact on changing health-related behaviors. By synthesizing the evidence, this review provides valuable insights into the use and impact of the FBM in promoting behavior change in health, with implications for future research and practice. Objective: To investigate the application of the FBM within the health domain, focusing on its role in behavior change interventions. Methods: A comprehensive search of multiple databases, including MEDLINE/PubMed, Cochrane Library, Epistemonikos, and PsycINFO, was conducted to identify studies applying the FBM in health-related interventions. The search strategy incorporated terms related to the FBM, health behavior change, and relevant health outcomes, with no restrictions on publication date. Unpublished and grey literature was also searched. Eligibility criteria included studies that applied the FBM in health interventions and reported outcomes. The review followed PRISMA-ScR and SAGER guidelines to ensure comprehensive reporting and consideration of sex and gender variables. Data were synthesized using a narrative approach, summarizing findings descriptively and thematically. Results: Six studies met the inclusion criteria, covering sexual and reproductive health, vaccination, chronic disease management, general wellness, and healthcare adherence. The FBM was applied through motivation (anticipation, sensation, belonging), ability enhancement (reducing effort, increasing accessibility, integrating behaviors into routines), and prompts (reminders, calls to action, environmental cues). Effectiveness varied across studies. Gestational weight management reduced gestational diabetes (10.34% vs. 34.48%, p = 0.028), hypertension (3.45% vs. 27.59%, p = 0.030), and cesarean rates (41.38% vs. 72.41%, p = 0.017). HPV vaccination interventions increased intent to vaccinate (63.3–96.7%, p < 0.001), with 30% receiving the first dose within three months. Diabetes self-management improved dietary adherence (p = 0.04), physical activity (p = 0.005), and glucose monitoring (p = 0.02). Parental nutrition interventions increased knowledge (d = 1.07), beliefs (d = 0.61), and behavior change (d = 0.59). A vaginal birth intervention raised intention by 29% (p < 0.05). Conclusions: Our scoping review highlights the FBM as an effective framework for promoting health behavior change across various domains. By systematically applying motivation, ability, and prompts, FBM-based interventions demonstrated positive outcomes. However, limitations such as the lack of long-term follow-ups and sex- and gender-disaggregated data indicate areas for future research. Expanding its application to diverse populations, integrating digital health technologies, and addressing structural and cultural barriers will enhance its impact. Strengthening methodological rigor and comparative analyses with other behavior change models will further refine its effectiveness for broader public health applications. Despite its potential, the FBM remains underutilized in public health research. Trial registration: Open Science Framework osf.io/jpwxg. © The Author(s) 2025.